Experimental and numerical study of a half-scaled reinforced concrete building equipped with thermal break components subjected to seismic loading up to severe damage state. (1st June 2015) - Richard, Benjamin; Ile, Nicolas; Frau, Alberto; Ma, Amandine; Loiseau, Olivier; Giry, Cedric; Ragueneau, Frederic
Highlights: Shaking table tests are carried out on a RC structure with thermal break components. Thermal break components have no influence on the structural response. The numerical results are in satisfactory accordance with the experimental ones. Abstract: A half-scaled reinforced concrete (RC) structure designed with an irregular shape to exhibit coupling torsional/bending effects and equipped with thermal break components was subjected to seismic tests. The aim of the experimental campaign was to analyze the influence of the thermal break components on the overall behavior of the mock-up in order to close the gap between the thermal and the seismic requirements in case of strongly irregular RC structures. The analysis of the experimental results is supported by experimental/numerical comparisons using an homogenized constitutive law to describe the behavior of a representative volume element (RVE) of RC. The observations show that the thermal break components do not significantly modify the dynamic behavior of the RC structure and ensure almost the full load transfer between the shearwalls and the connected slabs.